2013
DOI: 10.1155/2013/603897
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Support Vector Machine to Predict Subclinical Mastitis in Dairy Cattle

Abstract: This study presented a potentially useful alternative approach to ascertain the presence of subclinical and clinical mastitis in dairy cows using support vector machine (SVM) techniques. The proposed method detected mastitis in a cross-sectional representative sample of Holstein dairy cattle milked using an automatic milking system. The study used such suspected indicators of mastitis as lactation rank, milk yield, electrical conductivity, average milking duration, and control season as input data. The output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 23 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…When such features were included in the training of the model, the AUC increased to 0.81, showing an improved performance of the RF approach on this dataset (Hidalgo et al, 2018). Mammadova and Keskin (2013) used SVMs to ascertain the presence of subclinical and clinical mastitis in dairy cattle. They used 346 (61 mastitis cases) measurements of milk yield, electrical conductivity, average milking duration and somatic cell count collected from February 2010 to April 2011 for 170 Holstein Friesian dairy cows.…”
Section: Prediction Of Disease Phenotypesmentioning
confidence: 99%
“…When such features were included in the training of the model, the AUC increased to 0.81, showing an improved performance of the RF approach on this dataset (Hidalgo et al, 2018). Mammadova and Keskin (2013) used SVMs to ascertain the presence of subclinical and clinical mastitis in dairy cattle. They used 346 (61 mastitis cases) measurements of milk yield, electrical conductivity, average milking duration and somatic cell count collected from February 2010 to April 2011 for 170 Holstein Friesian dairy cows.…”
Section: Prediction Of Disease Phenotypesmentioning
confidence: 99%
“…Thus, EC of milk is now being used increasingly in the dairy industry to detect mastitis (Mammadova and Keskin, 2013). Also, it is a well-known fact that mastitis is associated with increased conductivity of udder tissue and changes in ionic composition of milk.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical conductivity between the RF and the RR quarters of the third and more lactating cows was 1.06 mS/ cm higher in comparison to the adequate quarters of the first lactation cows (P<0.05). It was reported that the electrical conductivity of 5.5 mS/cm in milk was a threshold for the subclinical mastitis (Mammadova et al, 2013). Other researches reported that the electrical conductivity of milk ranged from 4.6 to 5.8 mS/cm in samples with somatic cell counts below 200.000/mL and variation in electrical conductivity of milk could be accepted as one of the key parameters in the milking system for health monitoring system of dairy cows (Juozaitienė et al, 2015).…”
Section: Resultsmentioning
confidence: 99%